2020
DOI: 10.1002/adfm.202001033
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of MAPbBr3 Single Crystal p‐n Photodiode and n‐p‐n Phototriode for Sensitive Light Detection Application

Abstract: In this study, MAPbBr3 single crystal (MSC) p‐n perovskite homojunction photodiode and n‐p‐n phototriode are successfully fabricated through controlled incorporation of Bi3+ ions in solution. Optoelectronic analysis reveals that the photodiode shows typical photovoltaic behavior and the best photovoltaic performance can be achieved when the n‐type MSC is grown in 0.3% Bi3+ feed solution. The as‐assembled p‐n MSC photovoltaic detector displays obvious sensitivity to 520 nm illumination, with a high responsivity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
39
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(40 citation statements)
references
References 51 publications
0
39
0
Order By: Relevance
“…where ε 0 = 8.85 × 10 −12 pF m −1 is the vacuum permittivity [43], ε is the static dielectric constant which is taken as 16.73 for Cs 2 AgBiBr 6 [42], e is the the charge quantity and d is the film thickness. In consequence, the defect density of the device without and with UV treatment is calculated to be 8.97 × 10 16 and 3.33 × 10 16 cm −3 , respectively.…”
Section: Uv-induced Performance Improvement Of the Cs 2 Agbibr 6 -Based Photodetectorsmentioning
confidence: 99%
“…where ε 0 = 8.85 × 10 −12 pF m −1 is the vacuum permittivity [43], ε is the static dielectric constant which is taken as 16.73 for Cs 2 AgBiBr 6 [42], e is the the charge quantity and d is the film thickness. In consequence, the defect density of the device without and with UV treatment is calculated to be 8.97 × 10 16 and 3.33 × 10 16 cm −3 , respectively.…”
Section: Uv-induced Performance Improvement Of the Cs 2 Agbibr 6 -Based Photodetectorsmentioning
confidence: 99%
“…The maximal photocurrent gain reaches up to 600, which is much higher than the BJTs prepared by other methods. [8,22]…”
Section: Introductionmentioning
confidence: 99%
“…Methylammonium lead bromine (MAPbBr 3 ) perovskite is a member of the hybrid lead halide perovskite family that holds particular interest because it exhibits higher moisture stability than MAPbI 3 , and a narrower band gap than MAPbCl 3 and therefore offers great potential for use in a wide variety of optoelectronic applications, such as solar cells and high-sensitivity photodetectors. Moreover, recent studies have demonstrated that MAPbBr 3 can exhibit unique optical nonlinearity and ferroelectric properties, which further extend the range of potential MAPbBr 3 applications. However, most studies have focused on the macroscopic properties of MAPbBr 3 perovskite materials and the properties of their corresponding optoelectronic devices, whereas detailed studies seeking to understand the molecular mechanisms responsible for these properties are rare.…”
Section: Introductionmentioning
confidence: 99%